Setting Sail for a Sustainable Growth in Small/Medium Ports - Argyriou, Ioannis; Nisiforou, Olympia A.; Tsoutsos, Theocharis (My University, 2025)
Small- and medium-sized ports (SMSPs) face multifaceted challenges, including environmental pressures (pollution, resource depletion) as well as socio-economic strains (community impacts, trade dynamics). Governance complexities, regulatory fragmentation, limited funding, and stakeholder conflicts further exacerbate these challenges. This study identifies context-driven sustainability indicators for SMSPs and proposes best practices to enhance their resilience. Four small/medium-sized ports (SMSPs) in Crete, Greece—Souda (CHA), Heraklion (HER), Rethymnon (RET), and Sitia (SIT)—were evaluated to benchmark their sustainability performance using tailored indicators. The primary objectives were the following: (a) to identify sustainability indicators relevant to SMSPs, focusing on economic, environmental, and social aspects, and (b) to propose best practices for enhancing sustainability in these ports, considering their unique characteristics and constraints. A combination of the Best Worst Method (BWM) and VlseKriterijumska Optimizacija I Kompromisno Resenje (VIKOR) analysis was employed. The findings revealed that “environmental monitoring and management” and “security of employment and social protection” are top priorities for medium-sized ports, while “competitiveness” was a crucial indicator for small ports, emphasizing the need for financial sustainability in the context of global trade. These results offer a strategic roadmap for policymakers, guiding interventions aimed at improving the sustainability and resilience of SMSPs, thereby supporting regional economies and international trade networks.
Keywords: multi-criteria analysis; sustainable decision-making; sustainable ports; indicators; green evaluation